Ocorrência de Centris (Hemisiella) vittata Lepeletier (Hymenoptera: Apidae: Centridini) no Cerrado s.l. do nordeste do Maranhão, Brasil Occurrence of Centris (Hemisiella) vittata Lepeletier (Hymenoptera: Apidae: Centridini ) in the Cerrado s.l. Bioma of Maranhão, Northeastern Brazil - Marina da Costa Ramos; Márcia Maria Correia Rêgo; Patrícia Maia Corrêa de Albuquerque (Acta Amazonica, 2007)
Fêmeas de Centris vittata Lepeletier foram observadas visitando flores de Byrsonima sp. e nidificando em troncos de Astronium sp. (Anacardiaceae) em uma área de Mata Mesofítica, em Urbano Santos (3º 12' 28''S; 43º24'12''), Maranhão, Brasil. Females of Centris (Hemisiella) vittata Lepeletier were observed visiting flowers of Byrsonima sp. (Malpighiaceae) and nesting in Astronium sp. (Anacardiaceae) in a mesophytic forest area at Urbano Santos, Maranhão, Northeastern Brazil.